The Geography of Linguistic Diversity and the Provision of Public Goods - Klaus Desmet; Joseph Gomes; Ignacio Ortu\~no-Ortín (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper theoretically analyzes and empirically investigates the importance of local interaction between individuals of different linguistic groups for the provision of public goods at the national level. Depending on whether local interaction mitigates or reinforces antagonism towards other groups, the micro-founded theory we develop predicts that a country's provision of public goods (i) decreases in its overall linguistic fractionalization, and (ii) either increases or decreases in how much individuals locally learn about other groups. After constructing a 5 km by 5 km geographic dataset on language use for 223 countries, we compute measures of overall fractionalization and local learning, and investigate their relation to public good provision at the country level. While overall fractionalization worsens outcomes, we find a positive causal relation between local learning and public goods. Local mixing therefore mitigates the negative impact of a country's overall linguistic fractionalization. An IV strategy shows that this result is not driven by the possible endogenous spatial distribution of language speakers within countries.
Keywords: 330